IHE at 100: 25 Years of Evolution in International Higher Education - Schendel, Rebecca; Woldegiyorgis, Ayenachew; Khajarian, Araz (International Higher Education, 2020)
In this article, we summarize key findings from a comprehensive analysis of all of the articles included in the first 99 issues of International Higher Education. We find that the articles in IHE represent a very broad geographic reach, both in terms of article focus and author affiliation, and cover a wide variety of topics. However, some topics and regions have hardly been covered and deserve attention in future issues.